PERANCANGAN SISTEM KUNCI ELEKTRONIK BERBASIS MIKROKONTROLER AT89C52 - Briliant Adhi Prabowo; HerIan HerIan (Pusbindiklat - LIPI, 2009)
The access security awareness using conventional keys was less practical and much risky of leaving or even loosing the keys. Besides, access can not be locked automatically whenever the authentic user forgets to lock the door. The purposed of this research was to develop the electronic lock system design using personal identification number (PIN). Using PIN as an access key will give an easier method for the authenticated user without decreasing security level, and also it is more practical and easier since the authentic user doesn't need any key at all. This electronic lock design uses microcontroller AT89C52 for main control of the system which could be implemented on restricted area like laboratories or residences as well. More than 6000 PIN data can be saved in the serial memory 24LC65, and it will be accessed when the user enter the correct PIN.